2016
DOI: 10.1002/elps.201600365
|View full text |Cite
|
Sign up to set email alerts
|

Automation of DNA and miRNA co‐extraction for miRNA‐based identification of human body fluids and tissues

Abstract: In the last years, microRNA (miRNA) analysis came into focus in the field of forensic genetics. Yet, no standardized and recommendable protocols for co-isolation of miRNA and DNA from forensic relevant samples have been developed so far. Hence, this study evaluated the performance of an automated Maxwell® 16 System-based strategy (Promega) for co-extraction of DNA and miRNA from forensically relevant (blood and saliva) samples compared to (semi-)manual extraction methods. Three procedures were compared on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The minor risk of contamination, the higher reproducibility, and the economic time use are the main advantages of automated systems compared to manual isolation protocols. Moreover, automated extraction methods yielded the highest miRNA amounts from blood samples and the highest efficiency compared to manual protocols 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The minor risk of contamination, the higher reproducibility, and the economic time use are the main advantages of automated systems compared to manual isolation protocols. Moreover, automated extraction methods yielded the highest miRNA amounts from blood samples and the highest efficiency compared to manual protocols 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies include DNase treatment as a step in a proposed RNA analysis protocol, while others have included it as a type of negative control or do not specify any DNase treatment being performed (). We observed that DNase‐treated extracts were less than or equal to one cycle different from untreated extracts for all isolation methods.…”
Section: Resultsmentioning
confidence: 99%
“…A series of studies have reported that changes of miRNAs observed in certain biological fluids correlate with various pathological conditions suggesting that circulating miRNAs might be useful and informative biomarkers to reflect the pathological status of the body (Valentino et al, 2017 ; Wang, 2017 ; Zendjabil et al, 2017 ; Zhao et al, 2017 ). Evidence has emerged that miRNAs in blood or cerebrospinal fluid may serve as potential biomarkers of brain injury (Weber et al, 2010 ; Kulstein et al, 2016 ; Martinez and Peplow, 2016 ; Sirker et al, 2016 ; Wang, 2017 ). These miRNAs in biological fluids may come through the damaged blood–brain barrier after epilepsy onset or originate from controlled release in exosomes (Choi et al, 2017 ; Gourlay et al, 2017 ).…”
Section: Microrna and Epilepsymentioning
confidence: 99%